Brincando de detetive: uma investigação da relação entre o conteúdo e os fãs do podcast “Projeto Humanos” - Ferreira, Gabriella de Oliveira Salmeron (2024)
Being an expanding and highly popular genre in Brazil, 'True Crime' refers to infotainment products that bring true cases of real crimes and expose the details of crimes through films, series, documentaries, podcasts and many others. Available on several media aggregators since 2015, the investigative podcast Projeto Humanos defines itself as a storytelling podcast dedicated to telling real stories of real people and had as one of its main highlights one of the most shocking cases of the 90s, the Evandro Case. This master's research seeks to investigate how fans of the True Crime genre engage with criminal cases and how their active participation and engagement generates the phenomenon of fan-detectives from the study of the podcast "Projeto Humanos'' with the analysis of the discussion around the podcast in the Reddit community dedicated to product discussion.